Does inter-local cooperation reduce the intensity of tax competition? Evidence on inter-local industrial parks in Germany - Ivo Bischoff; Reinhold Kosfeld (Philipps-University Marburg, School of Business and Economics, 2021)
We ask whether inter-municipal cooperation serve as a platform by which municipalities coor-dinate tax policies and reduce the intensity of tax competition. In this paper, we focus on inter-municipal cooperation in form of inter-local industrial parks. We apply the generalized syn-thetic control method to analyze the causal impact of inter-local industrial parks on municipal tax-setting behavior using data on municipalities from four West-German states between 2000 and 2018. The analysis does not support the notion that inter-local industrial parks constitute a platform used for tax coordination.
Keywords: H25; H77; H71; R58; 330; Inter-local industrial parks; inter-municipal cooperation; tax competition; generalized synthetic control method; Germany